LEGAL RESPONSIBILITY OF GOODS/SERVICES PROVIDER FOR BUILDING FAILURE - Tulus Yudi Widodo Wibowo; Syofyan Hadi (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2023)
Construction failure can be caused by a failure in the process of procuring goods or services, or it may occur during the construction process itself. Construction work failure refers to a condition where the results of construction work do not comply with the agreed work specifications in the construction work contract, either partially or entirely, due to the fault of the service user or service provider. The purpose of this study is to analyze the responsibility of goods/services providers in the event of a building failure and to examine the form of their responsibility in such cases. This study adopts a descriptive normative approach to answer questions regarding the responsibilities of goods/services providers in cases of building failures, as outlined in Legislation Number 18 of 1999 concerning Construction Services, which was renewed as Number 2 of 2017 Construction Services, Government Regulation Number 29 of 2000 concerning construction service providers, and regulations pertaining to the responsibilities of goods/services providers in the event of building failures, which include meeting the Standards for Security, Safety, Health, and Sustainability, undergoing inspection by a team of experts appointed directly by the Minister, and complying within a maximum period of 10 (ten) years from the final delivery of Construction Services. The responsibility of goods/services providers for building failures is based on the principle of Liability based on Fault and is administered through written warnings, administrative fines, temporary suspension of construction service activities, inclusion in the black list, and even suspension or revocation of permits.